1999
DOI: 10.1152/ajpcell.1999.277.3.c432
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular elasticity and viscosity in the body, leading, and trailing regions of locomoting neutrophils

Abstract: To investigate the mechanisms underlying pseudopod protrusion in locomoting neutrophils, we measured the intracellular stiffness and viscosity in the leading region, main body, and trailing region from displacements of oscillating intracellular granules driven with an optical trap. Experiments were done in control conditions and after treatment with cytochalasin D or nocodazole. We found 1) in the body and trailing region, the granules divided into a “fixed” population (too stiff to measure) and a “free” popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
4
22
2
Order By: Relevance
“…Coincidentally, the protrusional stiffness of passive neutrophils measured here is very close in magnitude to the intracellular uniaxial stiffness of crawling neutrophils measured by Yanai et al (47). Furthermore, the characteristic relaxation time shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Coincidentally, the protrusional stiffness of passive neutrophils measured here is very close in magnitude to the intracellular uniaxial stiffness of crawling neutrophils measured by Yanai et al (47). Furthermore, the characteristic relaxation time shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The variation in the steady-state deprotonated-to-protonated SNARF-1 ratio may be due to actual pH cyt differences, variations in regional cytoplasmic microviscosity (28, 43,55,66), or even a different proportion of dye bound to cytoplasmic proteins (4). To properly interpret the differences in SNARF-1 protonated-to-deprotonated ratios, we have taken into account the behavior of the pH fluoroprobe in the cytoplasm, because it is heterogeneous in terms of composition and organization.…”
Section: Discussionmentioning
confidence: 99%
“…Although the oscillatory mechanics of reconstituted gels of the cytoskeletal filaments have been well studied (24,32,36), there have been relatively few investigations of the oscillatory mechanics of the intact living cell. In studies of the oscillatory mechanics, the cell was probed with the use of a variety of techniques: through the cell surface by atomic force microscopy (46), from the interior by oscillating intracellular granuoles using laser tracking (60), along the cell longitudinal axis using glass manipulators (47), or in a cell pellet using oscillating disk rheometry (12,23). However, no study has yet reported the oscillatory mechanics of the cell by accessing the cytoskeleton through direct attachments to focal adhesions.…”
mentioning
confidence: 99%